Determination of plasmid stability, pRSOD extraction and SOD production by recombinant Escherichia coli / Wan Siti Atikah Wan Omar ... [et al.] - Wan Omar, Wan Siti Atikah; Mohamed, Rosfarizan; Abdul Rahim, Raha; Ariff, Arbakariya (Universiti Teknologi MARA Cawangan Pahang, 2008)
A preliminary study of Escherichia coli harbouring super oxidedismutase (ESOD) was carried out to ensure the capability of the recombinant to achieve protein production in large scale cultivation process. The objectives of this study are first, to determine the stability of the plasmid in the recombinant E. coli, and later, the pRSOD and SOD production After the confirmation of the availability of the plasmid, the determination of medium composition was performed to choose the best medium for highest dry cell weight (dcw). The findings indicate that the ESOD successfully carried the plasmid (pRSOD) compared with other control references, E. coli BL21 (DE3) pLysS and E. coli BL21 (DE3) pLysS pRSET A. The ESOD also achieved 100% stability over 48 generations. The SOD was also found capable to produce a reasonable amount of SOD. Thus, the study has established that the ESOD is clearly comparable to other recombinant E. coli and suitable to pursue large scale process for high cell density cultivation.